2019
DOI: 10.31344/ijhhs.v3i3.91
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Study to elucidate the Effects of Artemisia afra, Aspalathus linearis (rooibos) and SeptilinTM on Immune Pathways

Abstract: Objective: Herbal immunomodulatory preparations are increasing in popularity. In vitro, in vivo and clinical trial studies are needed to ensure safety, quality and efficacy of these herbal medicines. SeptilinTM, a proprietary herbal medicinal product has been reported to have immunomodulatory effects. Aspalathus linearis (rooibos) is a commercialised South African (SA) tea recognised for its phytopharmaceutical potential. Artemisia afra is a well known SA herbal medicine used for various inflammatory condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Several in vitro and in vivo studies on the individual ingredients of Septilin TM were conducted on various models with varying effects on NO activity. Commiphora mukul, Rubia cordifolia, Emblica officinalis and Moringa pterygosperma has shown decreased NO secretion in previous studies 55,56 . Most studies of Tinospora cordifolia reported increased NO production.…”
Section: Immunomodulatory Studies On Septilin Tmmentioning
confidence: 77%
“…Several in vitro and in vivo studies on the individual ingredients of Septilin TM were conducted on various models with varying effects on NO activity. Commiphora mukul, Rubia cordifolia, Emblica officinalis and Moringa pterygosperma has shown decreased NO secretion in previous studies 55,56 . Most studies of Tinospora cordifolia reported increased NO production.…”
Section: Immunomodulatory Studies On Septilin Tmmentioning
confidence: 77%
“…Aspalathus linearis (rooibos) has gained popularity globally as an accepted nutraceutical. The health-promoting benefits of Aspalathus linearis (rooibos) have been confirmed in several in vitro and in vivo studies 16 . There are consistent reports on the safety of Aspalathus linearis (rooibos) 6 .…”
Section: Introductionmentioning
confidence: 83%
“…One study suggested that the minor component of Aspalathus linearis (rooibos) quercetin, is implicated in its possible mutagenic effects. However these effects were seen in concentration of 220-230 times more than that of the normal tea drinking quantities 16 . Aspalathin found in certain Aspalathus linearis (rooibos) extracts has been suggested to have anti-diabetic effects.…”
Section: Introductionmentioning
confidence: 86%
“…In South Africa Artemisia afra is a well-known herbal medicine used for various inflammatory conditions. [20][21][22][23] Hypertensives have higher interleukin-6 as per a study from Boston as shown by this graph…”
Section: Introductionmentioning
confidence: 94%